A vulnerabilidade ao consumo das mulheres tentantes após perdas gestacionais, neonatais ou infantis: o caso dos bebês arco-íris - Matos, Lívia Maria Teixeira (2024)
The objective of this research was to investigate the characteristics of consumption in health services by women who are trying to conceive and who have experienced one or more gestational, neonatal or infant losses. The justification for this work is to understand the consumption of these women in relation to a new pregnancy, based on theoretical approaches regarding consumer vulnerability, women trying to conceive, rainbow babies, grief and traumatic experiences. A qualitative study was conducted, with data collection through three techniques: focus groups, semi-structured interviews and non-participant observation. The data were analyzed through content analysis. The results suggest that there is a lack of specific structure for women trying to conceive within hospitals, maternity wards and clinics, and that depending on the health problem that the woman trying to conceive has, her vulnerability to consumption may be exacerbated. It is also implied that women trying to conceive use the consumption recommendations of women who are already pregnant in order to have the rainbow baby, in addition to opting for anonymity on social networks. According to the results of the analysis, it is inferred that religiosity can be considered a restorative consumption for grieving women who are trying to conceive. This study contributes to the literature by exploring consumer vulnerability in a multidisciplinary way, relating the perspective of consumption during mourning and traumatic experiences. In addition, it innovates by addressing the phenomenon of increased consumption associated with the term rainbow baby and its possible influences on social networks.